El uso de las técnicas grafo plásticas para fortalecer la motricidad fina de los niños de 4 a 5 años del centro de desarrollo integral Tagua, de la ciudad de Loja. Período lectivo 2017-2018 - Alejandro Cuenca, Jackson Salvador (2018)
This thesis is being entitled: THE USE OF PLASTIC GRAFO TECHNIQUES TO STRENGTHEN THE FINE MOTOR OF CHILDREN FROM 4 TO 5 YEARS OF THE INTEGRAL DEVELOPMENT CENTER TAGUA, OF THE CITY OF LOJA. PERIOD 2017 - 2018. The general objective of this study is to determine the plastic graph techniques to fortify fine motor skills in children from 4 to 5 years old, it is a qualitative study with a descriptive-explanatory focusing which pretends promoting the use of these techniques. The used methods were scientific, analytical-synthetic, and descriptive; Among the techniques and instruments used there were direct observation, the Goodard Dexterimeter Test and the survey guided to the teachers. The total population was 35 people, from which 17 fellows, 12 children and 5 teachers were taken as a sample, it was done by direct observation and according to the present motor difficulties. Regarding to the results in the pre-test it was found that 17% of the total population has a good psychomotor coefficient, 42% regular, 25% deficient and 16% has very poor. In this initial diagnosis it was possible to determine that 60% of the teachers state that graph-plastic techniques strengthen fine motor skills and 40% mention that creativity is being developed. After the intervention and with the execution of the alternative proposal, an 80% improvement was achieved, according to the analyzed, is concluded that there is a necessity to execute activities within the classroom to favor of the fine motor area development.